Tolerance of face coverings for children with autism spectrum disorder. Issue 2 (26th March 2021) - Halbur, Mary; Kodak, Tiffany; McKee, Marisa; Carroll, Regina; Preas, Elizabeth; Reidy, Jessi; Cordeiro, Maria Clara
Abstract : Healthcare professionals and government officials have advised the use of personal protective equipment, such as face masks and face shields, to assist with limiting the spread of the SARS‐CoV‐2 (COVID‐19). Due to the prevalence of challenging behavior associated with other medical routines, the present study evaluated a treatment package composed of graduated exposure, prompts, reinforcement, and escape extinction on tolerance of wearing a face covering for up to 5 min for 12 children with ASD in a systematic replication of Cox et al. (2017) and Sivaraman et al. (2020). We also extended previous research by measuring generalization of face covering type (i.e., face shield) and the efficacy of a treatment extension for tolerating a face covering for up to 15 min during the participants' trial‐based instruction and play periods.